Participation of The Community of Sekura Village, Teluk Keramat District, Sambas District in Participating The Family Planning Program - Endang Indri Listiani; Hasan Almutahar; Eka Apriyani; Elyta, Elyta (International Journal of Technology and Education Research, 2024)
The Sekura Village community in Sambas has shown significant participation in the Family Planning program, which promotes reproductive health and empowers families to make informed decisions about their children's number and spacing. Local health authorities have conducted comprehensive awareness campaigns, disseminating information about various family planning methods and their benefits. Regular workshops and seminars have dispelled myths and misconceptions, fostering open dialogue. Accessible health facilities have made it easier to access family planning services, and trained healthcare professionals have encouraged informed decisions. The program's inclusivity, respecting diverse cultural and religious perspectives, has fostered a sense of ownership and acceptance. Community leaders and local influencers have also played a crucial role in advocating for the program, breaking down cultural barriers and encouraging more individuals and families to embrace family planning as a positive and responsible choice. The robust participation of the Sekura Village community in the program can be attributed to effective awareness campaigns, accessible healthcare services, cultural sensitivity, and community leadership involvement.